GLOBAL DYNAMICS OF A COMPUTER VIRUS PROPAGATION MODEL WITH FEEDBACK CONTROLS - Dang, Quang A; Hoang, Manh Tuan; Tran, Dinh Hung (Journal of Computer Science and Cybernetics, 2020)
A computer virus propagation model with feedback controls is first proposed and investigated. We show that the control variables do not influence on the global stability of the original differential model, they only alter the position of the unique viral equilibrium. The mathematical analyses and numerical simulations show that this equilibrium can be completely eliminated, namely, moved to the origin of coordinates if suitable values of the control variables are chosen. In the other words, the control variables are effective in the prevention of viruses in computer systems. Some numerical simulations are presented to demonstrate the validity of the obtained theoretical results.